HESS J1640-465-an exceptionally luminous TeV γ-ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The results of follow-up observations of the TeV γ-ray source HESS J1640-465 from 2004 to 2011 with the High Energy Stereoscopic System (HESS) are reported in this work. The spectrum is well described by an exponential cut-offpower law with photon index γ = 2.11 ± 0.09 ± 0.10, and a cut-offenergy of E = 6.0 TeV. The TeV emission is significantly extended and overlaps with the northwestern part of the shell of the SNR G338.3-0.0. The new HESS results, a re-analysis of archival XMM-Newton data and multiwavelength observations suggest that a significant part of the γ-ray emission from HESS J1640-465 originates in the supernova remnant shell. In a hadronic scenario, as suggested by the smooth connection of the GeV and TeV spectra, the product of total proton energy and mean target density could be as high as W 4 × 10(d/10kpc) erg cm. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: G338.3-0.0-ISM; Individual objects; Non-thermal-ISM; Radiation mechanisms; Supernova remnants